Iodinated contrast media cause endothelial damage leading to vasoconstriction of human and rat vasa recta - Sendeski, Mauricio M.; Persson, Anja Bondke; Liu, Zhi Zhao; Busch, Jonas F.; Weikert, Steffen; Persson, Pontus B.; Hippenstiel, Stefan; Patzak, Andreas (American journal of physiology. Renal physiology, 2012)
Contrast-induced acute kidney injury is an important clinical event with a worldwide increasing number of cases. Medullary hypoperfusion and hypoxia due to constriction of vasa recta are main factors in the pathophysiology of acute kidney injury. However, the mechanism of contrast media (CM)-induced vessel constriction is not known. We tested the hypothesis that vasa recta constriction is a consequence of endothelial dysfunction due to the cytotoxicity of CM. Human and rat descending vasa recta (DVR) were isolated and perfused with CM, and the luminal diameter was analyzed. For morphological analysis of the endothelium, renal arteries were CM perfused and then processed for electron microscopy. Transcellular electrical resistance was used to estimate CM-induced changes in the permeability of human umbilical vein endothelial cell (HUVEC) layers. Perfusion with CM constricted human and rat DRV (to 54.3 and 50.9% of initial diameter, respectively). This was blunted by adrenomedullin (77.7 and 77.1%, respectively). The ANG II response was enhanced by CM in rat DVR (reduction to 15.6 and 35.0% of initial diameter, respectively). Adrenomedullin blunted this effect (67.5%). CM led to endothelial damage of renal arteries characterized by a ragged surface, with sharply protruding intimal folds, spindle-like shape, and bulging in the lumen. These phenomena were reduced by adrenomedullin. The permeability of HUVEC cell layers was increased by CM, and this went along with increased myosin light chain phosporylation. Again, adremonedullin reduced the CM effect. Our study suggests that the constrictor effect of CM on the renal medullary microvasculature is a consequence of endothelial cell damage and the resulting endothelial dysfunction.